Kritik Sastra Pragmatik Pada Film 1 Kakak 7 Ponakan Karya Arswendo Atmowiloto - Diana, Ani; Habibah, Ulul; Kholifah, Devi Nur; Nurhayati, Kholis; Apriyani, Chintia (Universitas Negeri Padang, 2025)
This study aims to analyze the moral, social, and aesthetic values contained in the film 1 Kakak 7 Ponakan by Arswendo Atmowiloto through a pragmatic literary criticism approach. This approach was chosen because it emphasizes the relationship between literary works and their audiences, and assesses the effects they have on the recipients of the message, both in terms of usefulness and aesthetic experience. The research method used is qualitative with documentation techniques, where data is obtained from the film as the main source. The results show that this film displays the values of responsibility, compassion, tolerance, and togetherness that shape the moral and social awareness of the audience, and presents the beauty of language and visuals that strengthen the aesthetic experience. Thus, this film functions not only as entertainment, but also as an effective educational medium to convey life messages. This study provides implications that film can be used as a medium for moral and character learning, and opens up opportunities for further research on audience responses and comparisons with other literary works.Keywords: Pragmatic Literary Criticism, Moral Values, 1 Kakak 7 Ponakan film